Statistical Analysis of Threat Detection Framework for Securing Semantic Web Amenities - Singh, Nagendra Kumar; Nayak, Sandeep Kumar; Faisal, Mohammad (International Journal of Psychosocial Rehabilitation, 2020)
The emergence of semantic web amenities has momentously streamlined accustomed life. Semantic web amenities have emerged as a medium through which conformist people can access various types of amenities quite easily. Digital trade is an emerging semantic web service that millions of users use in daily life. Through these amenities, the user acquires various types of information, as well as shares his confidential information. These amenities use assortments of database programs that preserve disparate types of data. That is why it is necessary that assorted types of database programs are used instead of the one type of database program to preserve disparate types of data available on semantic Web amenities. In this research paper, the utility of various types of database programs to preserve different types of data is explained through statistical analysis. In this paper, the chi-square test is used for statistical analysis. This paper shows how a single database program is not relevant to preserving different types of data and also shows how different types of database programs are capable of unprecedented increases in the functionality of semantic web amenities.